Big science Ernest Lawrence and the invention that launched the military-industrial complex - Hiltzik, Michael (Simon & Schuster, 2015)
The birth of Big Science can be traced to Berkeley, California, nearly nine decades ago, when a resourceful young scientist with a talent for physics and an even greater talent for promotion pondered his new invention and declared, 'I'm going to be famous!' Ernest Orlando Lawrence's cyclotron would revolutionize nuclear physics, but that was only the beginning of its impact. Its influence would be felt in academia and international politics. It was the beginning of Big Science.